2018
DOI: 10.3389/fpsyt.2018.00231
|View full text |Cite
|
Sign up to set email alerts
|

Prescription and Underprescription of Clozapine in Dutch Ambulatory Care

Abstract: Purpose: To our knowledge, no study has examined in a structured way the extent of underprescription of clozapine in ambulatory patients with Non-Affective Psychotic Disorder (NAPD). In the Netherlands, psychiatric care for such patients is provided by Flexible Assertive Community Treatment (FACT) teams and by early intervention teams. In 20 FACT teams and 3 early intervention teams we assessed the proportion of patients who: use clozapine (type 1 patients), previously used this drug (type 2), have an unfulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…Assuming the prevalence of treatment resistance is about 30%, the prescription rate in Denmark is about 15%. In The Netherlands prescription rates are relatively high (21.6%) (van der Zalm et al, 2018), which may explain the less restrictive use in patients with somatic comorbidity.…”
Section: Interpretation and Comparison To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming the prevalence of treatment resistance is about 30%, the prescription rate in Denmark is about 15%. In The Netherlands prescription rates are relatively high (21.6%) (van der Zalm et al, 2018), which may explain the less restrictive use in patients with somatic comorbidity.…”
Section: Interpretation and Comparison To Other Studiesmentioning
confidence: 99%
“…Surprisingly, a recent meta-analysis (Vermeulen et al, 2019) found a significantly decreased mortality during clozapine use [mortality rate ratio: 0.56; 95% confidence interval (CI): 0.36-0.85; P = 0.007). However, as we discussed earlier (van der Zalm et al, 2019), the results of this meta-analysis may be biased because the effect sizes had not been adjusted for age. Nevertheless, some studies (Tiihonen et al, 2009;Hayes et al, 2015) using age-adjusted effect measures reported a decreased mortality during the use of clozapine compared with the use of other antipsychotics.…”
Section: Introductionmentioning
confidence: 97%
“…Das atypische Antipsychotikum Clozapin hat einen besonderen Stellenwert in der Therapie von Psychosen aus dem schizophrenen Formenkreis. Leitlinien empfehlen Clozapin bei Therapieresistenz [1][2][3], außerdem wird es unter anderem bei assoziierten Symptomen, wie: extrapyramidale Bewegungsstörungen [4] , aggressives Verhalten [5] und Suizidalität [6] verordnet. Seit den Publikationen von Naber und Kollegen aus den 1990er-Jahren [7,8]…”
Section: Introductionunclassified
“…Since the foundation of the DCCG, the number of Dutch outpatients on clozapine has increased from 7764 in 2004 to 14 628 in 2019, an increase of 88%, which compares favourably with the 36% increase in the number of patients on other antipsychotics during the same period (15). In the Netherlands in 2016, the mean prescription rate of clozapine in 20 flexible assertive community (FACT) teams treating 2286 schizophrenia-spectrum patients was 23.0% (16). Nevertheless, 6.9% of the schizophrenia-spectrum patients who were eligible for clozapine treatment were not receiving it (range 1.7-15.6 %).…”
mentioning
confidence: 99%